2019
DOI: 10.1186/s12961-019-0502-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation: defining and exploring a concept to enhance the impact of public health initiatives

Abstract: Background: Repeated, data-driven optimisation processes have been applied in many fields to rapidly transform the performance of products, processes and interventions. While such processes may similarly be employed to enhance the impact of public health initiatives, optimisation has not been defined in the context of public health and there has been little exploration of its key concepts. Methods: We used a modified, three-round Delphi study with an international group of researchers, public health policy-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
2
31
0
Order By: Relevance
“…The deviation in implementation (i.e., program drift) that occurs as interventions move from the pilot/efficacy phase to the effectiveness/replication phase typically results in decreasing benefits for participants [ 22 ]. Comprehensive process evaluations can help to explain the process of implementation and guide intervention optimisation, defined by Wolfenden and colleagues [ 23 ] (pg. 5) as, “a deliberate, iterative and data-driven process to improve a health intervention and/or its implementation to meet stakeholder-defined public health impacts within resource constraints”.…”
Section: Introductionmentioning
confidence: 99%
“…The deviation in implementation (i.e., program drift) that occurs as interventions move from the pilot/efficacy phase to the effectiveness/replication phase typically results in decreasing benefits for participants [ 22 ]. Comprehensive process evaluations can help to explain the process of implementation and guide intervention optimisation, defined by Wolfenden and colleagues [ 23 ] (pg. 5) as, “a deliberate, iterative and data-driven process to improve a health intervention and/or its implementation to meet stakeholder-defined public health impacts within resource constraints”.…”
Section: Introductionmentioning
confidence: 99%
“…The predominant focus on optimising intervention effectiveness is unsurprising given that the main goal of public health interventions are to produce positive health outcomes for the population. However, a recent qualitative study examining optimisation of health care innovations in public health found that it was important for outcomes of the optimisation process to be determined by key stakeholders and end-users of the intervention to generate the greatest impact [13]. Previous studies have reported that stakeholders, typically agencies and organisations that fund the implementation or delivery of interventions, often consider many outcomes in addition to effectiveness, including cost, appropriateness to context and reach, when determining whether an intervention is suitable for translation or scaling up at a population level [13].…”
Section: Discussionmentioning
confidence: 99%
“…1. They report a framework describing a process of optimisation defined as a "deliberate, iterative and data-driven process to improve a health intervention and/or its implementation to meet stakeholderdefined public health impacts within resource constraints" [13]. 2.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations